Maya Gods of War - Bassie-Sweet, Karen (University Press of Colorado, 2021)
Numerous archaeological projects have found substantial evidence of the military nature of Maya society, and warfare is a frequent theme of Maya art. Maya Gods of War investigates the Classic period Maya gods who were associated with weapons of war and the flint and obsidian from which those weapons were made. Author Karen Bassie-Sweet traces the semantic markers used to distinguish flint from other types of stone, surveys various types of Chahk thunderbolt deities and their relationship to flint weapons, and explores the connection between lightning and the ruling elite. Additional chapters review these fire and solar deities and their roles in Maya warfare and examine the nature and manifestations of the Central Mexican thunderbolt god Tlaloc, his incorporation into the Maya pantheon, and his identification with meteors and obsidian weapons. Finally, Bassie-Sweet addresses the characteristics of the deity God L, his role as an obsidian merchant god, and his close association with the ancient land route between the highland Guatemalan obsidian sources and the lowlands. Through analysis of the nature of the Teotihuacán deities and exploration of the ways in which these gods were introduced into the Maya region and incorporated into the Maya worldview, Maya Gods of War offers new insights into the relationship between warfare and religious beliefs in Mesoamerica. This significant work will be of interest to scholars of Maya religion and iconography.